Proposta de um modelo baseado em blended learning para trilhas de aprendizagem por competências - CHAGAS, Rosana Augusto (Universidade Fernando Pessoa, 2023)
Aiming to equip the training area of public organizations with a computerized device that provides the development of strategic skills for organizations and, at the same time, stimulate their employees with the perspective of flexibility in choosing the type and modality most appropriate to their way of learning, the work described in this thesis was carried out, applying the action research methodology with a comparative contribution of the experience of four Brazilian organizations that are reference in the areas of training and learning trails. For this purpose, the following were used two mechanism: the decomposition of skills and the template adapted from the Instructional Design Made Easy model (Bruce, 1997, 1999, 2004), to elaborate questions to be used before and after contact with the didactic material of the learning activities, with the purpose of testing the achievement of the instructional objective, which pointed to an increase in the repertoire of the participants and made it possible to plan and design a computerized blended learning trails module to compose a computerized competence management system, in use since 2014. Thus, the prototype of the competency learning trails module, developed in the context of this project, waits the stabilization of the global health crisis caused by COVID-19 and the return of the activities of the Organizational Behavior Management Laboratory to be tested and, in the future. Implanted and implemented under the assumption that it also meets the precepts of risk management established by the Brazilian federal public administration.